A multicentre synergistic polyoxometalate-based metal–organic framework for one-step selective oxidative cleavage of β-O-4 lignin model compounds. Issue 1 (10th December 2019) - Tian, Hong-Rui; Liu, Yi-Wei; Zhang, Zhong; Liu, Shu-Mei; Dang, Tian-Yi; Li, Xiao-Hui; Sun, Xiu-Wei; Lu, Ying; Liu, Shu-Xia
Abstract : NENU-MV-5 as a heterogeneous catalyst without any co-catalyst, one-step selective oxidative cleavage of lignin models to high-value-added aromatics in a single solvent was achieved by synergistic effect of V IV –O–V V and Cu I using O2 as oxidant. Abstract : A novel mixed-valence polyoxovanadate-based copper–organic framework, [Cu I (bbi)]2 [Cu I (bbi)]2 VIV2V V 8 O26 ·2H2 O (NENU-MV-5, bbi = 1, 1′-(1, 4-butanediyl)bis(imidazole)), was facilely synthesized from routine reagents under mild hydrothermal conditions. Using NENU-MV-5 as a heterogeneous catalyst without any co-catalyst, one-step oxidative cleavage of β-O-4 lignin into phenols and aromatic acids with high catalytic activity and selectivity was realized under an oxygen atmosphere. No obvious decrease in activity was observed after five cycles, which indicates the excellent stability and sustainability of NENU-MV-5. The perfect catalytic performance of NENU-MV-5 can be attributed to the multi-site synergistic effect of the mixed-valence V V –O–V IV sites on polyoxovanadate for the oxidation of β-O-4 alcohol to β-O-4 ketone and the Cu(i ) sites on the framework for the rapid cleavage of the Cα –Cβ bond of β-O-4 ketone. This system represented the first co-catalyst-free example for the one-step selective degradation of lignin catalyzed by a well-defined crystalline catalyst with definite composition and structure in a single solvent.